Burmeister's work on Scoliidae with especial reference to types and synonymy (Hymenoptera: Scoliidae). - Bradley, James Chester; Betrem, Johan George (Contributions to Entomology = Beiträge zur Entomologie, 1966)
The two authors have independently studied the Scoliidae of the Burmeister collection in the University of Halle. Professor Bradley was solely concerned with identifying holotypes and selecting lectotypes of Burmeister's species. The results, along with the currently correct nomenclature of each nominal species, are recorded in the first part of this paper. Dr. Betrem has supplemented this with a study of the nominal Indo-Australian species of other authors recorded by Burmeister in his monograph. He has listed the correct identification and current name of each of these. Nomenclatural Actsleefmansi Betrem, 1928 (Campsomeriella), syn. n. of Campsomeriella agilis Smithcampestris (Burmeister, 1854) (Campsomeris (Aelocampsomeris)), Lectotype described as Scolia campestrislimosa (Burmeister, 1854) (Campsomeris (Xanthocampsomeris)), Lectotype described as Scolia limosamelanosoma (Saussure, 1859) (Carinoscolia), comb. n. hitherto Scolia melanosomaerythrosoma (Burmeister, 1854) (Liacos), comb. n. hitherto Scolia erythrosoma Burmeister, 1854capitata (Burmeister, 1854) (Microscolia), comb. n. hitherto Scolia capitata Burmeister, 1854aulica Burmeister, 1854 (Scolia), Lectotype now a synonym of Scolia (Discolia) dubia Sayfervida Burmeister, 1854 (Scolia), Lectotypefimbriata Burmeister, 1854 (Scolia), Lectotype now a synonym of Campsomeriella collaris aureicollis (Fabricius, 1775)fulvofimbriata Burmeister, 1854 (Scolia), Lectotypefulvopilosa Banks, 1912 (Scolia), syn. n. of Campsomeris (Xanthocampsomeris) limosá (Burmeister, 1854)guttata Burmeister, 1854 (Scolia), Lectotypemelanaria Burmeister, 1854 (Scolia), Lectotype now a synonym of Scolia (Discolia) ruficornis Fabriciuserythropyga Burmeister, 1854 (Scolia (Discolia)), Lectotypehaematodes (Burmeister, 1854) (Scolia (Discolia) dubia), Lectotype described as Scolia haematodes